The Relationship Between Students’ Attitudes Towards Mathematics Learning And Mathematical Communication Skills Of Students In Class VIII SMPN 1 Gunungsitoli Idanoi - Zebua, Etika; Lase, Sadiana (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine whether there is a relationship between students’ attitudes towards mathematics learning and mathematical communication skills of 8th grade students of SMPN 1 Gunungsitoli Idanoi. This type of research is quantitative research with an associative approach that aims to determine the relationship between two or more variables. The number of informants from this study was 186 students. Data collection techniques through student attitude questionnaire, and written test of mathematical communication ability. Based on this research, the results of hypothesis testing obtained thitung = 3.969 and ttabel 1.653. Because the hypothesis tcount = 3.969> ttable 1.653 then H0 is rejected H1 is accepted which means "There is a relationship between student attitudes on mathematics learning towards students’ mathematical communication skills this shows that there is a significant relationship between the attitudes of students in class VIII SMPN 1 Gunungsitoli Idanoi". So it can be concluded that students’ attitudes towards learning mathematics have a relationship to students’ mathematical communication skills.